The effects of the 2019 European commission’s green transition on transportation, housing, and food for ordinary citizens - Catarinella, Piermauro; Kram, Suhardi; Hashim, Aziz (2023)
Between the end of 2019 and the beginning of 2020, the European Commission, led by Ursula von der Leyen, along with other European institutions, approved the “European Green Deal” (EGD), an ambitious and idealistic project aimed at making Europe the first continent to achieve zero climate impact and transitioning all EU countries towards a sustainable economy. The EGD encompasses various aspects of human life, including industries, transportation, lifestyle, agriculture, and more. This study aims to explore how the EGD will impact the lives and wellbeing of citizens in three specific sectors: mobility, food, and housing. Citizens are being asked to undertake the following changes: 1) replace their internal combustion engine cars with non polluting vehicles; 2) retrofit their homes to improve energy efficiency and eliminate emissions; 3) adapt to a new food paradigm resulting from a comprehensive overhaul of the agro-food sector. Using an unbiased and analytical approach, this paper examines the nature of the EGD and assesses its perceived usefulness among the European populace, who bear the costly burden of the green transition, as not all EGD projects receive financial support from public institutions. Additionally, the study explores whether these changes benefit ordinary people or, conversely, lead to their significant impoverishment. The findings suggest that the EGD was a political decision driven by a convoluted political ideology and influenced by powerful entities seeking global control. This paper concludes that the opinions and expectations of ordinary citizens have been wholly disregarded, and their lives and well-being are expected to deteriorate. To address these issues, this qualitative research paper analyzes and interprets internal documents from the European Commission and the European Parliament, interviews with prominent politicians and scientists conducted across various media platforms, and recent articles published by Western newspapers.